Tree‐Ring Insights Into Past and Future Streamflow Variations in Beijing, Northern China - Honghua Cao; Feng Chen; Mao Hu; Tiyuan Hou; Xiaoen Zhao; Shijie Wang; Heli Zhang (Water Resources Research)
Abstract As the largest city in northern China and the capital of China, the rapid increases in Beijing’s water consumption in recent years have made water resources provision an increasing problem. To rationally allocate water resources, it is important to obtain long‐term runoff information in Beijing. In this study we develop a 236‐year chronology of tree‐ring widths based on cores from Pinus tabuliformis from four sampling sites. The resulting regression model reconstructs December–July runoff of the Yongding River in Beijing, with 49.5% of the variance explained, back to 1786 CE. Among the last 236 years, 1868, 1956, 1991, 1998, 2018, and 2021 were extremely high runoff years; and 1900, 1906, 1999, and 2000 were extremely low runoff years. Comparison of the runoff reconstruction results with climate grid data demonstrated a large magnitude of climate change in North China during the study period. Linkage analysis between the reconstructed runoff and large‐scale water vapor indicated that the high runoff years occurred during negative phases of the Pacific Decadal Oscillation, which may be influenced by the East Asian Summer Monsoon. Projections indicate that the flow of the Yongding River will increase in the future. Supported by policies such as the Ecological Water Supply and South‐to‐North Water Diversion, regional vegetation productivity and Yongding River runoff have increased substantially since 2000. Vegetation growth interacts with runoff volume. It is unclear how long these increases will continue.